Lip Hydration in Hemato-Oncologic Patients - Santos Pereira dos Reis, Sílvia Magda (2016)
Lips moisturizing within oral hygiene is of utmost importance in the care of oncology patients, in order to prevent possible changes in their integrity.The propose of this research was: to know lips moisturizing routine of the person with hematologic disease when receiving chemotherapy.This study is a quantitative approach, exploratory and across-sectional. The sample consisted of 54 subjects with hematologic disease receiving chemotherapy, who were admitted to a central hospital, between July 2013 to February 2014.The results of this study show that more than a half of these participants referred that they moisturized the lips, using moisturizing lipstick mostly. However, other products are referred such as cream, moisturizing lipstick and vaseline, or only vaseline.Nurses have to assume responsibility in training the person to self-care, allowing them to adopt preventive measures or minimize the oral mucositis, namely through teaching and training skills.